Penerapan VIKOR Method (VIšekriterijumsko KOmpromisno Rangiranje Method) Dalam Rekomendasi Pemilihan Laptop Gaming - Merriam Modeong; M. Ikbal Siami (Jurnal Ilmiah Computer Science, 2023)
The VIKOR method (VIšekriterijumsko KOmpromisno Rangiranje Method) is one of the techniques in the field of multi-criteria analysis used to make decisions in situations where there are several criteria that must be considered simultaneously. This method helps in decision making when there are many alternatives that must be evaluated based on several different criteria. The research conducted aims to provide recommendations to users in the selection of gaming laptops by applying a decision support system model using the VIšekriterijumsko KOmpromisno Rangiranje Method (VIKOR) method so that it becomes an input in the selection of gaming laptops. The final calculation results in the VIKOR method provide recommendations for Rank 1, namely Predator Helios 18 Laptop, Rank 2, namely ASUS ROG Zephyrus G14 Laptop, Rank 3, ASUS ROG Strix SCAR 18 Laptop, and Rank 4, Nitro 5 Laptop. The results of application testing using the black box testing method obtained a percentage result of 100% in accordance with the functions that have been created